The handbook of naturally occurring insecticidal toxins - Koul, Opender (CAB International, 2016)
This book on insecticidal toxins from natural sources is a complete review of the subject. Containing 500 chemical structures, it examines toxins from sources such as plants, microorganisms and marine flora and fauna and includes chapters on bioassays, concepts of insecticidal activity, structure activity relationships and commercial aspects.